Search for Possible Associations of FTO Gene Polymorphic Variants with Metabolic Syndrome, Obesity and Body Mass Index in Schizophrenia Patients - Boiko AS; Pozhidaev IV; Paderina DZ; Bocharova AV; Mednova IA; Fedorenko OY; Kornetova EG; Loonen AJM; Semke AV; Bokhan NA; Ivanova SA (Dove Medical Press, 2021)
Anastasiia S Boiko,1,* Ivan V Pozhidaev,1,* Diana Z Paderina,1 Anna V Bocharova,2 Irina A Mednova,1 Olga Yu Fedorenko,1 Elena G Kornetova,3,4 Anton JM Loonen,5 Arkadiy V Semke,3 Nikolay A Bokhan,6,7 Svetlana A Ivanova1,7 1Molecular Genetics and Biochemistry Laboratory, Mental Health Research Institute, Tomsk National Research Medical Center of the Russian Academy of Sciences, Tomsk, Russian Federation; 2Laboratory of Evolutionary Genetics, Research Institute of Medical Genetics, Tomsk National Research Medical Center of the Russian Academy of Sciences, Tomsk, Russian Federation; 3Endogenous Disorders Department, Mental Health Research Institute, Tomsk National Research Medical Center of the Russian Academy of Sciences, Tomsk, Russian Federation; 4University Hospital, Siberian State Medical University, Tomsk, Russian Federation; 5Unit of Pharmacotherapy, Epidemiology & Economics, Groningen Research Institute of Pharmacy, University of Groningen, Groningen, the Netherlands; 6Addictive Disorders Department, Mental Health Research Institute, Tomsk National Research Medical Center of the Russian Academy of Sciences, Tomsk, Russian Federation; 7Psychiatry, Addiction Psychiatry and Psychotherapy Department, Siberian State Medical University, Tomsk, Russian Federation*These authors contributed equally to this workCorrespondence: Anton JM LoonenUnit of Pharmacotherapy, Epidemiology & Economics, Groningen Research Institute of Pharmacy, University of Groningen, Antonius Deusinglaan 1, Groningen, 9713AV, the NetherlandsTel +31 50 363 7576Email a.j.m.loonen@rug.nlPurpose: Metabolic syndrome (MetS) is characterized by abdominal obesity, hyperglycaemia, dyslipidaemia and hypertension. FTO gene has been implicated in the pathogenesis of obesity, but the available scientific data concerning their relationship to antipsychotic drug-induced obesity and metabolic syndrome is still incomplete and inconsistent, which indicates that continuing the investigation of this gene's role is necessary.Patients and Methods: In the present study, 517 patients with schizophrenia underwent antipsychotic drug treatment, and two groups were identified: patients with MetS and without MetS. Genotyping of 6 SNPs in the FTO gene was performed, and the results analyzed using R-programme.Results: We performed a statistical analysis to identify possible associations of the frequencies of genotypes and alleles of the studied polymorphisms with the presence of metabolic syndrome in schizophrenia patients, with the presence of abdominal obesity, and with an increased body mass index. The rs7185735 polymorphism did not meet the Hardy-Weinberg criterion and was excluded. After correcting for differences in age, gender and duration of illnesses, none of the variants was shown to be related to metabolic syndrome or abdominal obesity, but rs9939609, rs1421085, rs3751812 and rs8050136 were associated with body mass index.Conclusion: The present study provides additional support for these SNP's roles as a pharmacogenetic biomarker that may become useful in the framework of the personalized medicine approach.Keywords: schizophrenia, gene polymorphism, body weight, waist circumference, fat mass and obesity associated gene